Diagnostic Value of Clinical and Laboratory Findings in Childhood Meningitis - Emiroglu, Melike; Kesli, Recep; Kilicaslan, Murat (Journal of Pediatric Infectious Diseases, 2020)
Objective Acute meningitis in childhood is a serious infectious disease that requires immediate medical assessment to ensure appropriate treatment and healthy outcomes. The aim of this retrospective study was to evaluate clinical and laboratory findings in the diagnosis of acute meningitis in children.Materials and Methods Between February 2011 and March 2013, 258 children aged between 1 month and 18 years who were admitted to Konya Training and Research Hospital, Turkey, with clinically suspected meningitis and undergoing lumbar puncture were enrolled in the study. Patient charts were reviewed using a standardized data collection tool. Fifty-nine patients were excluded because of incomplete data or because they did not meet the enrollment criteria. Further statistical analysis was conducted on the remaining 199 patients. The diagnostic values of clinical and laboratory findings for acute meningitis were investigated. IBM SPSS 21.0 for Windows was used for the statistical analysis.Results Of the 199 patients (61.3% male; median age: 24 months), 101 (50.8%) were diagnosed with meningitis. A definitive diagnosis of bacterial meningitis was made in 16 patients, while 5 patients had probable bacterial meningitis. In addition, 80 patients diagnosed as aseptic meningitis and 47 of these patients had human enterovirus meningitis. Headache was more common in patients with meningitis. In patients without meningitis, the most common complaints were seizures or seizures accompanied by fever. Erythrocyte sedimentation rates (ESR), levels of cerebrospinal fluid protein, and cell counts in cerebrospinal fluid examinations were higher in the meningitis group. C-reactive protein, ESR, and procalcitonin higher than 22.55 mg/L, 36.5 mm/hour, and 6.795 mg/mL, respectively, indicated bacterial meningitis.Conclusion Our results showed that a combination of clinical and laboratory markers could facilitate recognition of bacterial meningitis in children.
Keywords: meningitis; childhood; clinical findings; laboratory findings